Can Tactile Neglect Occur at an Intra-Limb Level? Vibrotactile Reaction Times in Patients with Right Hemisphere Damage - J. B. Mattingley; J. L. Bradshaw (Behavioural Neurology)
Visual reaction time (RT) studies on patients with right hemisphere (RH) damage have demonstrated that the attentional imbalance to stimuli occupying left and right positions exists even within the “intact” ipsilesional hemifield. The purpose of the present study was to test whether such patients might also exhibit relative left-sided impairments in the tactile modality, where stimuli and responses involve the index and middle fingers of the non-hemiplegic ipsilesional hand. Eight patients with RH damage, and eight matched normal controls, were tested using a vibrotactile choice RT paradigm, with the responding hand held in prone or supine posture, and located either at the body midline, or in left or right hemispace. Patients showed significantly slower RTs with the left than the right finger in both hand postures, a difference which remained constant as a function of the hemispatial location of the responding hand. In the prone posture, patients' left finger RTs were slower than those of controls, who showed no difference between left and right finger RTs, while their right finger RTs were faster than those of controls. In the supine posture, both patients and controls exhibited slower left than right finger RTs, though in controls the left finger disadvantage was attributed to biomechanical rather than attentional factors. Patients also made more errors with left than right finger stimuli, both as failures of detection and as incorrect responses, while controls made fewer errors overall and showed no differences between fingers. These data demonstrate a bias in the distribution of attention to tactile stimuli at an intra-limb level, and suggest that the attentional imbalance created by RH damage may be supramodal.